Overhead Umbrella Art Installation in Rovaniemi, Finland ... - Campbell, Sandy (University of Alberta Library, 2018)
Strings of lime green umbrellas with white swans criss-cross the street in front of the Arctic Lights Hotel in Rovaniemi, Finland, celebrating the 2018 Arctic Art and Summer Design event. ...